Consumer-side actions in a low-carbon economy: A dynamic CGE analysis for Spain. (July 2018) - Duarte, Rosa; Sánchez-Chóliz, Julio; Sarasa, Cristina
Abstract: In recent decades, the need to strengthen efforts to reduce GHG emissions to combat Climate Change has become a major global concern, as reflected in the 2015 Paris Agreement and the EU Climate strategy (2016). In this context, EU countries are required to organize their contributions to environmental improvement through national strategies. Given the potential importance of demand-side actions, both directly and through their relationship with the productive system, as well as the need for a dynamic evolution, we assess the dynamic path and medium-term environmental impact of certain consumer-oriented measures, using a dynamic Computable General Equilibrium (CGE) model. Specifically, we generate scenarios that follow Spain's strategies and evaluate the dynamic impact of more efficient technologies on electricity consumption and the use of transport services, both in terms of environmental (GHG and SOx ) and economic effects. Our results confirm the role of technology improvements in delivering positive results for the environment, and the importance of economy-wide rebound effects, through a detailed study of energy uses as a result of efficiency improvements in household energy consumption. Our findings show that reductions in emissions per person are consistent with economic growth. Highlights: Two improvements in the efficiency of household energy use are evaluated. Gradual effects up to 2030 are modelled using logistic functions. Reductions in emissions per person are consistent with economic growth. Economy-wide rebound effects and impacts on emissions reveal significance.